2020
DOI: 10.1002/cplu.202000191
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Synthesis of Porous Carbons and Their Applications in Catalysis

Abstract: Porous carbons have shown considerable potential in catalysis as either as supports or metal-free catalysts. Various methods based on solution chemistry have been intensively developed for the preparation of porous carbon-based catalysts with controllable morphology, pore structure, surface chemical property as well as the desired active sites. Nowadays, mechanochemical synthesis, a re-emerging strategy, has become more and more popular in the synthesis of porous carbons, due to its feasibility and high synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…The finding of Zhang et al. that ball milling can sustain the coordinative cross‐linking polymerization of tannin with divalent metal ions (as metal acetates, e.g., Zn 2+ , Ni 2+ , and Co 2+ ) in the presence of a template (e.g., Pluronic triblock copolymers) lead to the synthesis of various ordered mesoporous carbons [75] . Indeed, the use of templates with different compositions simply enabled the synthesis of mesoporous carbons with tuneable pore sizes, ranging from 4 to 10 nm, after carbonization of the gel nanocomposite [76] .…”
Section: Metal and Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…The finding of Zhang et al. that ball milling can sustain the coordinative cross‐linking polymerization of tannin with divalent metal ions (as metal acetates, e.g., Zn 2+ , Ni 2+ , and Co 2+ ) in the presence of a template (e.g., Pluronic triblock copolymers) lead to the synthesis of various ordered mesoporous carbons [75] . Indeed, the use of templates with different compositions simply enabled the synthesis of mesoporous carbons with tuneable pore sizes, ranging from 4 to 10 nm, after carbonization of the gel nanocomposite [76] .…”
Section: Metal and Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…Mechanochemistry promotes chemical reactions through the mechanical force obtained by grinding, shearing, stretching, and so forth 18−20 and is widely applied in organic synthesis 21,22 such as ladderane/ene, 23 metal−organic frameworks, 24 and deep eutectic solvents; 25 inorganic synthesis like noble metal nanoparticles, 26 supported metal catalysts, 27 and γ-graphyne; 28,29 gas synthesis 30 such as CH 4 , 31 CO 2 , 32,33 and CO; 34 highly porous materials; and so forth. 35,36 In as early as 1996, Mori et •h −1 under 45 °C and 1 bar, demonstrating that the mechanochemistry is a promising nitrogen fixation technology. 38 The NH 3 synthesis process was divided into two steps of nitrogen dissociation and hydrogenation; it successfully elucidated the mechanism of gas phase mechanochemical synthesis of NH 3 in detail (Figure S1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Mechanochemistry promotes chemical reactions through the mechanical force obtained by grinding, shearing, stretching, and so forth and is widely applied in organic synthesis , such as ladderane/ene, metal–organic frameworks, and deep eutectic solvents; inorganic synthesis like noble metal nanoparticles, supported metal catalysts, and γ-graphyne; , gas synthesis such as CH 4 , CO 2 , , and CO; highly porous materials; and so forth. , In as early as 1996, Mori et al reported methanation of CO 2 in the ball mill and revealed the value of continuous heterogeneous catalyzed gas-phase reactions under ball milling conditions, demonstrating that Ru–MgO and Ni–Fe–MgO are superior to other evaluated catalysts in facilitating the mechanochemical methanation of CO 2 in a ball milling process . In 2011, Mulas et al demonstrated the mechanochemical hydrogenation of carbon monoxide over FeCo- and Mg 2 Ni-based catalysts, confirming that the mechanical activation at 300 K and 0.6 MPa outperformed standard thermal methods (400–800 K, 2–5 MPa) by realizing similar or higher conversion .…”
Section: Introductionmentioning
confidence: 99%
“…These parameters are of particular importance in the design and preparation of advanced materials for a range of catalytic applications. There are many reports on the use of mechanochemical protocols to obtain various catalysts (supported metal nanoparticles, nanocomposites, and nanomaterials) with improved catalytic activity and selectivity 24 , 26 , 27 , demonstrating the potential of this method to provide more sustainable routes for the preparation of catalysts 28 .…”
Section: Introductionmentioning
confidence: 99%